Responses of Broilers under Cold Conditioning (15°C) to Dietary Triiodothyronine and Iodine Combined to Antioxidants (Selenium and Vitamin C) - Seven, Ismail; Seven, Pinar Tatli; Yilmaz, Seval (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
This experiment was conducted to determine the influence of dietary antioxidants (selenium (Se) and vitamin C). and triiodothyronine (T-3) to iodine on biochemical parameters. malondialdehyde (MDA). catalase (CAT) in broilers exposed cold. In the study, 150. one-day-old, broiler chicks (Ross 308) were used. Chicks were randomized into I control and 4 treated groups each containing 30 birds and each experimental group comprised 3 replicates of 10 birds The experimental groups were as follow: control was fed with basal diet: group I was fed with basal diet supplemented with 1 mg/kg selenium as sodium selenite plus 2 mg/kg iodine as calcium iodate: group II was fed with basal diet supplemented 1 mg/kg selenium plus 1 mg/kg T-3: group III was fed with basal diet supplemented with 250 mg/kg vitamin C as ascorbic acid plus I mg/kg iodine: group IV was fed with basal diet supplemented with 250 mg/kg vitamin C plus 1 mg/kg T-3. Plasma T-3, triglyceride and SGPT were significantly different among the groups. MDA level in heart tissue of control group was found significantly higher than those of other groups (P < 0.01). MDA levels in liver (P < 0.01) and abdominal fat (P < 0.001) tissues of control and group I were determined significantly higher than those of other groups, whereas MDA level in lung tissue was similar found in all groups The CAT activity of liver of control and group I was found significantly the highest (P < 0.001) Results showed that cold exposure in broilers induced oxidative damage in tissues. but this damage decreased partly in supplement groups, except group 1.
Keywords: Cold conditioning; Antioxidant enzymes; Iodine; Ascorbic acid; Selenium; Triiodothyronine; Broiler